Laminar-specific distribution of zinc: Evidence for presence of layer IV in forelimb motor cortex in the rat - Alaverdashvili, M.; Hackett, Mark; Pickering, I.; Paterson, P. (Academic Press, 2014)
© 2014 Elsevier Inc.The rat is the most widely studied pre-clinical model system of various neurological and neurodegenerative disorders affecting hand function. Although brain injury to the forelimb region of the motor cortex in rats mostly induces behavioral abnormalities in motor control of hand movements, behavioral deficits in the sensory-motor domain are also observed. This questions the prevailing view that cortical layer IV, a recipient of sensory information from the thalamus, is absent in rat motor cortex. Because zinc-containing neurons are generally not found in pathways that run from the thalamus, an absence of zinc (Zn) in a cortical layer would be suggestive of sensory input from the thalamus. To test this hypothesis, we used synchrotron micro X-ray fluorescence imaging to measure Zn distribution across cortical layers. Zn maps revealed a heterogeneous layered Zn distribution in primary and secondary motor cortices of the forelimb region in the adult rat. Two wider bands with elevated Zn content were separated by a narrow band having reduced Zn content, and this was evident in two rat strains. The Zn distribution pattern was comparable to that in sensorimotor cortex, which is known to contain a well demarcated layer IV. Juxtaposition of Zn maps and the images of brain stained for Nissl bodies revealed a "Zn valley" in primary motor cortex, apparently starting at the ventral border of pyramidal layer III and ending at the close vicinity of layer V. This finding indicates the presence of a conspicuous cortical layer between layers III and V, i.e. layer IV, the presence of which previously has been disputed. The results have implications for the use of rat models to investigate human brain function and neuropathology, such as after stroke. The presence of layer IV in the forelimb region of the motor cortex suggests that therapeutic interventions used in rat models of motor cortex injury should target functional abnormalities in both motor and sensory domains. The finding is also critical for future investigation of the biochemical mechanisms through which therapeutic interventions can enhance neural plasticity, particularly through Zn dependent pathways.